Study on Technical Differences in Sea Boundary Determination Based on Permendagri No. 1/2006, Permendagri No. 76/2012 and Permendagri No. 141/2017 - Luhur Moekti Prayogo; Joko Eddy Sukoco (JURNAL PERIKANAN DAN KELAUTAN, 2021)
The sea boundary is an authority in managing marine environmental resources that aim to limit each local government's management. The Indonesian government has made various regulations in regulating regional boundaries, including maritime boundaries. This study aims to determine the differences in the determination of sea boundaries that have been regulated in the Permendagri, including Permendagri No. 1 of 2006, Permendagri No. 76 of 2012, and Permendagri No. 141 of 2017. This research is limited to the study of literature articles that regulate the determination of the boundaries of marine areas. Permendagri No.1 of 2006 and Permendagri No. 76 of 2012 explained that the authority over the management of marine resources is managed by the regions. While in Permendagri No. 141 of 2017 explained that the management of marine resources is regulated by law. The study results found that three critical points of change are listed in the Permendagri, including the use of base points, the use of cartometric methods, and the authority of sea management by districts/cities. From this research, it can be concluded that the Regency/City no longer has the authority to manage marine resources. However, the affirmation of the 4-mile sea boundary for the Regency/City is still needed to calculate the profit-sharing for the management of marine resources. Determination of the base point in the affirmation of boundaries no longer uses the lowest low tide but uses the highest tide as stated in Permendagri No. 141 of 2017. The affirmation of maritime boundaries using the cartometric method has begun to be applied to Permendagri No. 76 of 2012 and continued in Permendagri No. 141 of 2017.